DETERMINAN UNDERPRICING SAHAM GO PUBLIC TAHUN 2009-2013 - Yanti, Emi; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
The firms go public conduct Initial Public Offering (IPO) and set price of its shares with underwriters . Underpricing phenomenon that occurs when IPO is influenced by several factors. This study aims to determine the effect Return On Assets (ROA), firm size , underwriter reputation, auditor reputation, firm  age, and financial industry type to the IPO underpricing. Total population of firms IPO in 2009-2013 are 115 firms and obtained 90 samples , with a purposive sampling method. The analysis technique is multiple linear regression analysis with SPSS. The results showed that only auditor reputation negatively affect s underpricing. Underwriter reputation negatively affect s underpricing but the research hypothesis was rejected because different direction. ROA, firm size, firm age and financial industry type have no effect on underpricing. This suggests that non-financial information especially auditor reputation affect s underpricing because investors believe that audited financial statements have informed the company as a whole.
Keywords: underpricing, IPO, financial information, non-financial information